STABILIZING REINFORCED PEAT USING CALCIUM-BASED ADDITIVE (SH85) - Noraida, Razali; Norazzlina, M.Sa'don; Abdul Razak, Abdul Karim (School of Engineering. Taylor’s University, 2024)
Due to its low shear strength, high compressibility, and bearing capacity, peat is classified as problematic soil and has become a major issue in construction development. This peaty soil presented geotechnical challenges due to its instability and rapid rate of settlement. In this study, shredded rubber crumb (RC) was added to peat (Pt) extract from Kota Samarahan, Sarawak, Malaysia, at regulated percentages of 5%, 10%, and 15%. Cement (C) that act as a binder added at a constant percentage of 5% with 3% to 6% powdered calcium-based resin (SH-85) that serve as an additive. The reinforced peat was prepared at the optimum moisture content for all design mix and cured for 7, 28, and 56 days at room temperature before tested for unconfined compressive strength (UCS) test. California bearing ratio (CBR) test specimens were cured for 7 and 28 days before the test was conducted. The findings indicate that UCS of 398.9 kPa was reached with the design mix of Pt+5%C+10%RC+3%SH-85 over a 7-days curing period. This was approximately 35 times higher than the strength of untreated soil. Whereas the maximum strength was 513.3 kPa for soil mixed with 5%C+15%RC+6%SH-85 after 56 days of curing. Results of the CBR test shows that the design mix of Pt+5%C+5%RC+3%SH-85, exhibit the highest strength of the reinforced peat which is 28.3% at 28-days curing period. It exceeds the minimum CBR value requirement between 5% and 12% stated by Public Works Department (PWD), Malaysia. This study also analysed the microstructure of the treated peat soil. Images taken by scanning electron microscopy (SEM) shows that the voids in treated peat have been significantly reduced and occupied by the new component formed by the interaction of peat with SH-85 and cement. This resulted in a continuous soil fabric, which produced denser and stronger soil. The results of the laboratory tests showed that the treated peat soil increases soil shear strength and load-bearing capacity. Therefore, it is recommended that the stabilized peat can be used as a subgrade layers, as the addition of SH-85 and shredded rubber crumb improve peat engineering properties.